2015
DOI: 10.1039/c5nj02566d
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1,3,4-oxadiazole motifs bearing a quinoline nucleus: synthesis, characterization and biological evaluation of their antimicrobial, antitubercular, antimalarial and cytotoxic activities

Abstract: A series of quinoline based 1,3,4-oxadiazole derivatives 8a-l were synthesized by chloro-amine coupling reaction approach with different catalyst and solvents. The substituted 1,3,4-oxadiazole intermediates 7a-c were obtained from 2-sustituted-N-phenylhydrazinecarbothioamide 6a-c by cyclization with different cyclizing reagents like mercuric acetate, lead dioxide, iodobenzenediacetate (IBD) and aqueous sodium hydroxide with iodine in aqueous potassium iodide to isolate the most effective reaction condition by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Ladania GG et al synthesized new series of hits by coupling 1,3,4-oxadiazole with substituted quinoline moiety using molecular hybridization using different catalyst and solvents. 26 Primary screening of obtained compounds were performed against Mycobacterium tuberculosis H37Rv strain using Lowenstein-Jensen medium. The result showed that compounds 27(a-d) ( Figure 24) were found to possess excellent activity.…”
Section: Anti-alzheimer Activitymentioning
confidence: 99%
“…Ladania GG et al synthesized new series of hits by coupling 1,3,4-oxadiazole with substituted quinoline moiety using molecular hybridization using different catalyst and solvents. 26 Primary screening of obtained compounds were performed against Mycobacterium tuberculosis H37Rv strain using Lowenstein-Jensen medium. The result showed that compounds 27(a-d) ( Figure 24) were found to possess excellent activity.…”
Section: Anti-alzheimer Activitymentioning
confidence: 99%
“…[1][2][3] Several of these compounds containing the quinoline nucleus display innumerous biological properties and are used as drugs against malaria, cardiovascular diseases, allergies, and vasodilators. [4][5][6][7][8][9][10][11][12][13][14][15] The search for new drugs more potent and with less side effects requires chemical strategies of synthesis that facilitate the obtaining of intermediates for the construction of heterocycles in a quick way and in smaller reaction times, speeding up the process of the synthesis until the biological evaluation. [16] 4-Azo-butenolides are synthons for the synthesis of quinolines, dihydroquinolines, lactones, and a large amount of derivatives of great pharmacological interest.…”
Section: Introductionmentioning
confidence: 99%
“…Various derivatives of these types of heterocycle have previously revealed cytotoxic activity: 1,2,4-oxadiazole, 31 1,2,4-triazine, 32,33 1,2,3-triazole, 34 and furoxan itself. 13,14 Heterocyclic motifs, namely quinolines 35 and pyridines, 36 connected to the furoxan ring through O-bridges, are also found in compounds possessing cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%